Aging restricts the initial neural patterning potential of developing neural stem and progenitor cells in the adult brain - Saeideh Aran; Mohammad Ghasem Golmohammadi; Mohsen Sagha; Kamran Ghaedi (Frontiers in Aging Neuroscience)
IntroductionNeurosphere culture is widely used to expand neural stem and progenitor cells (NSPCs) of the nervous system. Understanding the identity of NSPCs, such as the principals involved in spatiotemporal patterning, will improve our chances of using NSPCs for neurodevelopmental and brain repair studies with the ability to direct NSPCs toward distinct fates. Some reports indicate that aging can affect the nature of NSPCs over time. Therefore, in this study, we aimed to investigate how the initial neural patterning of developing NSPCs changes over time.MethodsIn this research, evidence of changing neural patterning potential in the nervous system over time was presented. Thus, the embryonic and adult-derived NSPCs for cardinal characteristics were analyzed, and then, the expression of candidate genes related to neural patterning using real-time quantitative reverse transcription polymerase chain reaction (RT-qPCR) was evaluated at various stages of embryonic (E14 and E18), neonatal, and adult brains. Finally, it was assessed the effect of cell attachment and passage on the initial neural patterning of NSPCs.ResultsThe analysis of gene expression revealed that although temporal patterning is maintained in vitro, it shows a decrease over time. Embryonic NSPCs exhibited the highest potential for retaining regional identity than neonatal and adult NSPCs. Additionally, it was found that culture conditions, such as cell passaging and attachment status, could affect the initial neural patterning potential, resulting in a decrease over time.ConclusionOur study demonstrates that patterning potential decreases over time and aging imposes restrictions on preliminary neural patterning. These results emphasize the significance of patterning in the nervous system and the close relationship between patterning and fate determination, raising questions about the application of aged NSPCs in the treatment of neurodegenerative diseases.